Business Process Optimization Through the Implementation of Efficient Organizational Management - Mendrofa, Septi Juarnita; Rahmani, Nur Ahmadi Bi; Hayati, Fitri (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2024)
In the dynamic business environment, companies must continually adapt and enhance their processes to maintain or elevate their competitiveness. This study explores how the implementation of efficient organizational management can optimize business processes and contribute to achieving a competitive edge. Utilizing a focus group and discussion approach, the research involved qualitative data collection through discussions with senior managers, operational staff, and management team members. The study examined key aspects such as adaptive organizational structures, responsive management practices, and the fostering of a supportive work culture. The findings reveal that efficient organizational management is critical for optimizing business processes. Key steps include in-depth analysis of business processes, identification of problem areas, setting clear goals and KPIs, and implementing suitable technology and information systems. Additionally, employee training and development, cultural transformation, and rewards and recognition play significant roles in enhancing performance and efficiency